Transformation of the modern states - Гайко, О. С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The transformation of the modern states is discussed in terms of changes in traditional state functions and the emergence of an alternative organizational structures. The genesis of regular armies and social policy is analized. The main emphasis is made on such problems as changes in war nature, growing influence of international organizations and corporations, gradual loss of the state monopoly on violence and deregulation process.